An investigation into factors determining the metering performance of a fuel control unit in an aero engine. (March 2020) - Yuan, Yuan; Zhang, Tianhong; Lin, Zhonglin; Zhang, Jiaming
Abstract: Fuel flow rate is the most important and most used control parameter for aero engines and it is assured by a device called the fuel control unit (FCU). To investigate factors that determine the metering performance of the fuel control unit, this research comes into being. This paper establishes mathematical models revealing the effect of these determinants, which are pressure difference across the metering valve and actuating process of the metering valve. Results show that the pressure difference does not keep constant as we thought. It will influence the accuracy of metered fuel of the fuel control unit. Furthermore, factors such as the input current of the servo valve, the pressure of the servo fuel and the moving direction of the metering valve will have impacts on the actuating process of the metering valve, influencing the dynamic response of the fuel control unit. Finally, the analyses are affirmed in a hardware-in-the-loop (HIL) experiment involving a real fuel control unit. Highlights: Determinants of the metering performance of a fuel control unit are modeled mathematically. The pressure difference across the metering valve may not maintain constant for a fuel control unit with constant pressure drop valve. The input current of servo valve, the pressure of servo fuel and moving direction of the metering valve have an impact on the dynamic response of the fuel control unit. Hardware-in-the-loop experiments involving a real fuel control unit are conducted to prove the investigation.